FINANCIAL MANAGEMENT STRATEGY OF CULINARY MSMES IN RESPONDING TO ECONOMIC INSTABILITY: A CASE STUDY IN AMUNTAI SELATAN SUB-DISTRICT - Ary Yudianto (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2025)
This study aims to analyze the financial management strategies implemented by micro, small, and medium-sized enterprises (MSMEs) in the culinary sector in response to economic instability in Amuntai Selatan. The research employed a qualitative approach using a case study method, involving five culinary MSME actors selected purposively. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data presentation, and inductive conclusion drawing techniques. The results indicate that the financial management strategies of culinary MSMEs are generally still simple and intuitive. Financial planning is rarely carried out formally, financial records are mostly done manually with varying quality, and financial control mainly relies on daily cash and stock monitoring without evaluation based on financial reports. The main challenges faced by MSME actors include low financial literacy, the absence of separation between business and personal finances, limited access to formal financing, and low utilization of digital technology. Nevertheless, MSME actors demonstrate adaptability through operational efficiency, simple product innovation, and the use of social media as a promotional tool. These findings highlight the importance of improving financial literacy, adopting digital financial recording technology, and strengthening support from relevant stakeholders to enhance the resilience of culinary MSMEs in facing economic dynamics